Dead men don't rape - Bolino, Pakito 1966-; Dom Tom 1961-; Sury, Caroline 1964-; Broutelles, Frédéric de; Colas 1971-; Kerozen 1968-; Poincelet, Frédéric 1967-; Blexbolex 1966-; Valium, Henriette 1959-2021; Y5/P5 1961-; Tjoyas, Alexios 1965-; Pigassou, Olivier; et al. (Amanita, 1993)
"Mug was not really a band, it was a collaborative project between a bunch of crazy musicians and crazy visual artists, they stayed three weeks together to write songs and record them on the spot, the result is that freak experimental record. Musically speaking, this is quirky, angular and noisy experimental arty punk, if i'm correct, the strings section is held by former members ot French Art Punk band La Machoire, and the drums by a guy from the Scottish band Badgewearer. The vinyl was released by the Amanita label and the silkscreened package done by Le Dernier Cri including an inbound booklet (also fully silkscreened). Due to the sheer amount of hand-made work to produce this baby, the pressing was limited to 500 copies... The booklet art was done by several undergraphists as Y5P5, Sury, De Broutelles, BlexBolex, Valium, Poincelet, Kerozen and others." (philippines80shardcore.blogspot.com)
Serigraphie. - Auflage 500 Exemplare
Tracklist: A1. Le Bras Du Traitre. - A2. Mr Pig Friend. - B1. Copulation Box. - B2. Arm Head Periscope. - C1. Lucy Elvira Jones. - C2. Black Pudding. - C3. Moroko Fingers. - C4. Steack House
Keywords: Graphzine; Schallplatte